Creating context for corridors of consumption: the case of Ireland. Issue 1 (1st January 2021) - Lavelle, Mary Jo; Fahy, Frances
Abstract: Global consumption levels are significant contributors to detrimental environmental change and the current climate crisis. Across Ireland, domestic consumption levels have increased dramatically during the past three decades. Public discourse has focused primarily on minimum levels of consumption, with media outlets frequently reporting on minimum wages and acceptable minimum levels of food, shelter, and healthcare. A dearth of dialogue exists on the concept of maximum levels of consumption. This article proffers that the concept of consumption corridors provides a timely lens to initiate discussion and to critically consider the potential of ascertaining maximum levels of consumption across Ireland. Drawing on analyses of an extensive database of 1, 500 households across two policy regions − Northern Ireland and the Republic of Ireland − we argue that there is no single universally just and ecologically sustainable way of setting limits to consumption. Numerous factors must be considered including scale, policy influences, cultural understandings, and varying expectations of standards of living and quality of life. The article reports on participants' perceptions of material items as needs and satisfiers and aims to advance methodological applications of the consumption-corridors concept. This study offers evidence highlighting a need for tailored sustainability policies.